Combining CBT and sertraline does not enhance outcomes for anxious youth: a double-blind randomised controlled trial. Issue 5 (31st August 2021) - Hudson, Jennifer L.; McLellan, Lauren F.; Eapen, Valsamma; Rapee, Ronald M.; Wuthrich, Viviana; Lyneham, Heidi J.
Abstract: Background: Anxiety disorders are the most prevalent mental disorder in children and young people. Developing effective therapy for these children is critical to reduce mental disorders across the lifespan. The study aimed to evaluate the efficacy of combining cognitive behavioural therapy (CBT) and sertraline (SERT) in the treatment of anxiety in youth, using a double-blind randomised control trial design. Methods: Ninety-nine youth (ages 7–15 years) with an anxiety disorder were randomly allocated to either individual (CBT) and SERT or individual CBT and pill placebo and assessed again immediately and 6 months after treatment. Results: There were no significant differences between conditions in remission of primary anxiety disorder or all anxiety disorders. Furthermore, there were no significant differences in rates of change in diagnostic severity, parent-reported anxiety symptoms, child-reported anxiety symptoms or life interference due to anxiety. Conclusions: The efficacy of CBT for children and adolescents with anxiety disorders is not significantly enhanced by combination with a short-term course of anti-depressants over and above the combined effects of pill placebo.